2021
DOI: 10.21037/apm-21-934
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of red blood cell distribution width level on histological response and prognosis in colorectal liver metastases

Abstract: Background:The red blood cell distribution width (RDW) level is a potential prognostic factor for solid tumours.We aimed to investigate the predictive value of pre-neoadjuvant chemotherapy (pre-NAC) RDW, preoperative RDW and the change in RDW on the pathological response and prognosis of patients with colorectal liver metastasis (CRLM), which was helpful for treatment decision-making, surveillance and prognostication.Methods: This retrospective study analyzed clinicopathologic data, treatments and outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…[30][31][32] In a recent study, RDW was shown to be a reliable marker that could predict pathological response after neoadjuvant chemotherapy in rectal cancer patients with liver metastasis. [14] The normal reference range of RDW-CV in blood cells is 11.5-15.4%. In our study, the optimal RDW-CV level was determined using ROC analysis to be 15%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] In a recent study, RDW was shown to be a reliable marker that could predict pathological response after neoadjuvant chemotherapy in rectal cancer patients with liver metastasis. [14] The normal reference range of RDW-CV in blood cells is 11.5-15.4%. In our study, the optimal RDW-CV level was determined using ROC analysis to be 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Among these hematologic parameters, both HB and RDW levels are valuable factors in predicting the pathological response and prognosis in malignancies receiving neoadjuvant therapies, especially in rectal cancer. [13,14] Although HB levels and RDW are successful parameters separately, it may be even more beneficial to combine them. The ratio of hemoglobin to red cell distribution width (HRR) reflects these two parameters simultaneously.…”
mentioning
confidence: 99%